Minimize effluents of aeration process in wastewater treatment plant - Yaw M.W.; Chong K.H.; Goh C.H.; Karmila K. (Alpha Publishers, 2023)
The aim for this paper is to optimize the water quality indicator which is the sewage effluent from aeration process in Wastewater Treatment Plant (WWTP) process by using hybrid Artificial Immune System (AIS) algorithm. The effluents are including dissolved oxygen (DO) and other effluents such as biochemical oxygen demand (CBOD), concentration of suspended solids (TSS), dissolved phosphorous (TDP) and suspended phosphorous (TSP). The proposed algorithms will be applied into model of aeration process in practical of WWTP process in this paper. The proposed AIS algorithms are named as Transform of Artificial Immune System (TRANSAIS) and Cross Three Parents of Artificial Immune System (X3PAIS). The two models are tested under the similar condition such as generation number, size of population, rate of cloning process, rate of mutation process, crossover rate and stopping condition. The concentration of the effluents will affect the water quality and energy consumption during WWTP process. The optimize indicators results from this paper will be used in the next research to optimize the energy consumption in WWTP process. 2020 Alpha Publishers.